Developing and Piloting the DEEP-ECE Model for Early Childhood Educators: A Professional Development Framework for Reflective Practice and Pedagogical Competence - Yafie, Evania; Atmoko, Adi; Sari, Zihan Novita; Ashari, Rahayu; Samah, Norazrena Abu (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
This study developed and piloted the DEEP-ECE model, or Deep Learning Based Curriculum Empowerment for Early Childhood Educators, as a professional development framework for supporting early childhood teachers in implementing pedagogical deep learning within Indonesia’s Merdeka Curriculum. The model was designed in response to a common problem in teacher professional development: training is often brief, fragmented, and insufficiently connected to classroom practice. Using a research and development design based on the ADDIE model, this study involved 15 kindergarten teachers from UM Laboratory Kindergarten. Data were collected through needs assessment questionnaires, semi-structured interviews, expert validation, practicality questionnaires, and pretest and posttest competence assessments. Quantitative data were analyzed using descriptive statistics, normality testing, paired sample t-tests, and correlation analysis, while qualitative feedback was used to clarify teachers’ needs and responses to the model. The results showed that DEEP-ECE was rated highly valid by experts and practical by participating teachers. Teachers’ professional competence increased significantly after the intervention, with a mean difference of 10.53 points, t = -9.471, p < .001, while pedagogical competence increased by 14.20 points, t = -15.072, p < .001. Pretest and posttest scores were also strongly correlated, indicating consistency in the competence measures rather than causal evidence of effectiveness. These findings suggest that DEEP-ECE has preliminary promise as a structured, reflective, and classroom based professional development model. Its broader contribution lies in offering a transferable design logic for early childhood teacher development in curriculum reform contexts where teachers are expected to enact meaningful, child centered, and reflective pedagogy. Further studies with larger samples, comparison groups, classroom observations, and longitudinal follow up are needed to examine the model’s effectiveness and sustainability.